Faktor Yang Mempengaruhi Pilihan Konsumen Pada Rumah Type 66 Di Kota Pontianak - Sumiyati, Sumiyati; Yulian, Ryani (JURNAL MANAJEMEN MOTIVASI, 2019)
This study  aimed to determine the effect of product quality, price, location, product knowledge,  reference group, investment, and company image on consumer choice in type 66 houses in Pontianak City. The results showed that product quality, price, location, product knowledge, reference group, and investment have positive and significant effect on consumer choice, while corporate image has a positive and insignificant effect on consumer choice. Product quality is the most dominant variable affecting consumer choice in buying type 66 houses in Pontianak City.